Development and support of small business in Kazakhstan - Bikhanova, A. S. (Journal of Economic Research & Business Administration, 2015)
In conditions of transformation economy of Kazakhstan small business plays a very important role both in the local economy and throughout the country, because actually the territorial specialization allowed him to complete small business “big” economy and form a relatively complete, integrated structure of the economy of regions, cities and rural areas. Small enterprises and, in General, small business occupied their niche in economic activities that most focused on regional and local needs. The implementation of state programs and business development will set the stage of formation and development of SMEs in Kazakhstan and has made this trend irreversible. Their implementation influenced positively on the formation and development of the business sector in the country. A competitive market for goods and services was created and institutional arrangements for support and development of small business were identified. Entrepreneurship in Kazakhstan is one of the priorities of the economic policy of the State, and the Government seeks to build the middle class and competitive dynamic business community.